2019
DOI: 10.1021/jacs.9b11424
|View full text |Cite
|
Sign up to set email alerts
|

Total Chemical Synthesis of a Nonfibrillating Human Glycoinsulin

Abstract: Glycosylation is an accepted strategy to improve the therapeutic value of peptide and protein drugs. Insulin and its analogues are life-saving drugs for all type I and 30% of type II diabetic patients. However, they can readily form fibrils which is a significant problem especially for their use in insulin pumps. Because of the solubilizing and hydration effects of sugars, it was thought that glycosylation of insulin could inhibit fibril formation and lead to a more stable formulation. Since enzymatic glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…A century of advances in insulin science has established much improved therapy that elevates the level of efficacy and safety that must be exceeded by any further change in insulin structure. An example in how these new methods might be employed can be witnessed most recently by a report from Wade and associates to prepare an insulin analog with an additional cysteine at the N-terminal B-chain that following glycosylation displayed appreciable bioactivity devoid of fibril formation and with improved plasma stability [27]. Alternatively, the previously discussed report from Brunel et al illustrates one approach toward the chemical optimization of the hormone in pursuit of glucoseresponsive insulin analogs [18].…”
Section: Discussionmentioning
confidence: 99%
“…A century of advances in insulin science has established much improved therapy that elevates the level of efficacy and safety that must be exceeded by any further change in insulin structure. An example in how these new methods might be employed can be witnessed most recently by a report from Wade and associates to prepare an insulin analog with an additional cysteine at the N-terminal B-chain that following glycosylation displayed appreciable bioactivity devoid of fibril formation and with improved plasma stability [27]. Alternatively, the previously discussed report from Brunel et al illustrates one approach toward the chemical optimization of the hormone in pursuit of glucoseresponsive insulin analogs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Using total chemical synthesis, insulin possessing an additional, orthogonally-protected Cys at the N-terminal of B-chain was synthesized to which a sialyloligosaccharide was selectively introduced. This sialo-glycoinsulin is an example of S-glycosylation, which, importantly, maintained native structure and in vivo blood glucose lowering activity (Hossain et al, 2020). Moreover, an S-glycan is reported to be more stable toward proteolysis than analogs of O-glycan (De Leon et al, 2017).…”
Section: Glycosylation Of Therapeutically Valuable Diabetes Peptide Drugsmentioning
confidence: 91%
“…A long-acting insulin analog was obtained by modification of insulin with dendritic sialyl oligosaccharide by an enzymatic method (Sato et al, 2004). In addition, insulin modified with sialylundecasaccharide (Figure 2) demonstrated excellent stability against fibrillation at high concentration and high temperature (Hossain et al, 2020). Using total chemical synthesis, insulin possessing an additional, orthogonally-protected Cys at the N-terminal of B-chain was synthesized to which a sialyloligosaccharide was selectively introduced.…”
Section: Glycosylation Of Therapeutically Valuable Diabetes Peptide Drugsmentioning
confidence: 99%
“…As described above, the structure-activity relationship study of N-glycans on EPO demonstrates the importance of the N-glycan structure on the bioavailability and bioactivity of proteins [115]. Hossain and Wade et al reported that the physical properties of insulin can be improved by adding N-glycan to insulin, which originally has no glycans [148]. Introduction of sialic acid containing N-glycans to insulin successfully inhibited problematic fibril formation.…”
Section: Next-generation Protein/peptide Drugs Modified With Homogenementioning
confidence: 97%